43 CARDIAC TROPONINS AND COVID-19: WHAT DO WE KNOW ABOUT HETEROPHILIC ANTIBODIES?. (15th December 2022) - Campana, Pasquale; Forzano, Imma; Pepe, Marco; Basile, Christian; Perillo, Errico Federico; Ranieri, Alessandro; Conte, Maddalena; Parisi, Valentina; Sibilio, Gerolamo
Abstract: Background: During the Coronavirus disease-19 (COVID-19) pandemic, a significant increase in cardiovascular events and death for acute Myocardial Infarction (AMI) has been widely described. In turn, cardiac troponins represent the main serum diagnostic biomarkers of AMI. However, several mechanisms of troponins elevation other than AMI could be identified such as the analytic interference due to the Heterophilic Antibodies (HA), which represents a less explored and underestimated cause. Methods: The research of the following keywords "Heterophilic" or "Heterophile Antibodies" associated with "Troponin", "Troponin I", "Troponin T" or "High-sensitive Troponin" have identified 73 works in the most popular bibliographic databases such as PubMed, Scopus, and Web of Science, in which the first was published in 1998. In our systematic review, the inclusion criteria have considered all the works in which clinical information about the patients are described. The results have included 55 papers for an overall population of 128 cases that have presented HA's interference in troponins' assay. In the great part of the works, HA's capture test has been performed to diagnose this interference. The association between HA and COVID-19 has also been explored with the identification of three works in scientific literature. In addition, we reported a clinical case of a young patient with persistent high serum ultra-sensitive Troponin levels due to HA, during the COVID-19 pandemic. Results: The results have indicated the most at-risk population in patients with a history of multiple hospitalizations and with poor cardiovascular risk factors, who usually complained of atypical chest pain combined with persistent elevation of cardiac troponins without high CK-MB values. Instead, only a few data could be isolated in the literature about HA's interference on troponins essay in COVID-19 patients. However, has been widely ascertained how increased serum levels of cardiac troponins have been identified in most of the SARS-COV-2 swabs positive populations, and several cardiac and extracardiac mechanisms may explain this condition. Conclusions: The description of the most common clinical features of patients with HA's interference could help clinicians to early recognize this phenomenon, reducing the number of instrumental examinations and the hospitalization period of these patients. Therefore, the analytical mistake due to HA could be always considered in AMI differential diagnosis, and the use of HA's capture test in the at-risk population may determine an early diagnosis. Finally, the HA's phenomenon could increase during the COVID-19 period, considering how infections and vaccinations may stimulate heterophile's activity.